The impact of the covid-19 pandemic on perceived diabetes care and regulation, with a focus on ethnic minorities: a mixed-methods study - Saskia E. van Grondelle; Bilal Güzel; Manon D. Mijnsbergen; Paul Uitewaal; Janet M. Kist; Sytske van Bruggen; Hedwig M. M. Vos; Mattijs E. Numans; Rimke C. Vos (BMC Primary Care)
Abstract Background This study aimed to explore the impact of the COVID-19 pandemic and resulting changes to diabetes care, especially concerning disease control, the use of (tele)consultation and lessons worth implementing to improve diabetes care, with a specific focus on ethnic minority groups. Methods A mixed-methods prospective cohort study among people with type 2 Diabetes Mellitus (T2DM) treated in primary care during the COVID-19 pandemic. A survey was sent regionally, including items related to teleconsultation and amount of contact with the healthcare professional. We conducted interviews based on the chronic care model with individuals from various ethnic backgrounds living in a deprived neighbourhood. Change in diabetes control (HbA1c, fasting glucose, LDL, systolic BP, BMI, eGFR) was evaluated based on routine care data. Latent class analysis was performed to identify groups who were more at risk for decreased glycaemic control. Results Most people maintained face-to-face (59%) or telephone (44%) contact with their healthcare provider. A decrease in consultations was observed. Based on the interviews, factors important for maintaining good glycaemic control were the use of medical devices, religion, routines and social support from family and friends. We did not find a clinically relevant change in diabetes control and no specific group was identified as at risk for worse diabetes regulation. Conclusions In the context of proactive care, remote healthcare and self-regulation have a crucial role for people with T2DM. It is important to identify barriers and facilitators for maintaining good glycaemic control among vulnerable groups, such as ethnic minority groups.